Molluscicidal Activity of Extracts and Fractions From Hagenia abyssinica, Rosa abyssinica, and Cucumis ficifolius Against Biomphalaria and Bulinus Snails - Hirut Basha; Asfaw Debella; Milkyas Endale; Eyob Debebe; Meharu Mathewos; Tesfaye Biftu; Hassen Mamo (Journal of Parasitology Research)
Conclusion: H. abyssinica demonstrated potent molluscicidal activity, making it a potential candidate for application. Further isolation of active ingredients and field trials are necessary to determine the optimal conditions for its use in snail control.